Changes in the U.S. Primary Standards for the Air Kerma From Gamma-Ray Beams - Seltzer, Stephen M. (J Res Natl Inst Stand Technol, 2003)
Monte Carlo photon-electron transport calculations have been done to derive new wall corrections for the six NBS-NIST standard graphite-wall, air-ionization cavity chambers that serve as the U.S. national primary standard for air kerma (and exposure) for gamma rays from (60)Co, (137)Cs, and (192)Ir sources. The data developed for and from these calculations have also been used to refine a number of other factors affecting the standards. The largest changes are due to the new wall corrections, and the total changes are +0.87 % to +1.11 % (depending on the chamber) for (60)Co beams, +0.64 % to +1.07 % (depending on the chamber) for (137)Cs beams, and −0.06 % for the single chamber used in the measurement of the standardized (192)Ir source. The primary standards for air kerma will be adjusted in the near future to reflect the changes in factors described in this work.